Redox Regulation of Heart Regeneration: An Evolutionary Tradeoff - Elhelaly, Waleed M.; Lam, Nicholas T.; Hamza, Mohamed; Xia, Shuda; Sadek, Hesham A. (Frontiers in Cell and Developmental Biology, 2016)
Heart failure is a costly and deadly disease, affecting over 23 million patients worldwide, half of which die within 5 years of diagnosis. The pathophysiological basis of heart failure is the inability of the adult heart to regenerate lost or damaged myocardium. Although limited myocyte turnover does occur in the adult heart, it is insufficient for restoration of contractile function (Nadal-Ginard, 2001; Laflamme et al., 2002; Quaini et al., 2002; Hsieh et al., 2007; Bergmann et al., 2009, 2012). In contrast to lower vertebrates (Poss et al., 2002; Poss, 2007; Jopling et al., 2010; Kikuchi et al., 2010; Chablais et al., 2011; González-Rosa et al., 2011; Heallen et al., 2011), adult mammalian heart cardiomyogenesis following injury is very limited (Nadal-Ginard, 2001; Laflamme et al., 2002; Quaini et al., 2002; Bergmann et al., 2009, 2012) and is insufficient to restore normal cardiac function. Studies in the late 90s elegantly mapped the DNA synthesis and cell cycle dynamics of the mammalian heart during development and following birth (Soonpaa et al., 1996; Soonpaa and Field, 1997, 1998), where they showed that DNA synthesis drops significantly around birth with low-level DNA synthesis few days after birth. Around P5 to P7, cardiomyocytes undergo a final round of DNA synthesis without cytokinesis, and the majority become binucleated and exit the cell cycle permanently. Therefore, due to the similarities between the immature mammalian heart and lower vertebrates (Poss, 2007; Walsh et al., 2010), it became important to determine whether they have similar regenerative abilities. Recently, we demonstrated that removal of up to 15% of the apex of the left ventricle of postnatal day 1 (P1) mice results in complete regeneration within 3 weeks without any measurable fibrosis and cardiac dysfunction (Porrello et al., 2011). This response is characterized by robust cardiomyocyte proliferation with gradual restoration of normal cardiac morphology. In addition to the histological evidence of proliferating myocytes, genetic fate-mapping studies confirmed that the majority of newly formed cardiomyocytes are derived from proliferation of preexisting cardiomyocytes (Porrello et al., 2011). More recently, we established an ischemic injury model where the left anterior descending coronary artery was ligated in P1 neonates (Porrello et al., 2013). The injury response was similar to the resection model, with robust cardiomyocyte proliferation throughout the myocardium, as well as restoration of normal morphology by 21 days. However, this regenerative capacity is lost by P7, after which injury results in the typical cardiomyocyte hypertrophy and scar-formation characteristic of the adult mammalian heart. Not surprisingly, the loss of this regenerative capacity coincides with binucleation and cell cycle exit of cardiomyocytes (Soonpaa et al., 1996; Walsh et al., 2010). An important approach toward a deeper understanding the loss of cardiac regenerative capacity in mammals is to first consider why, and not only how, this happens. Regeneration of the early postnatal heart following resection or ischemic infarction involves replacement of lost myocardium and vasculature with restoration of normal myocardial thickness and architecture, with long-term normalization of systolic function. Why would the heart permanently forego such a remarkable regenerative program shortly after birth? The answer may lie in within the fundamental principal of evolutionary tradeoff.